Ali Kouaouci Normes familiales isJamiques et fecondite en Jordanie, en Indonesie et au Pakistan. Recherches demographiques cahier nr 5. Departement de demographie, Universite catholique de Louvain. Louvain-Ia-Neuve, Belgium: Cabay Ltbraire-Editeur S. A., 1983.236 pp.B francs 500 paperback. ISBN 2-87077-143-6 (The Pakistan Development Review, 1990)
If the editor of this journal was given to that type C?f language slant, this review could begin with the question "Why is Pakistan fertility as low as it is?", or with the statement "Forty percent of Pakistan infertility is due to sterility"; or still differently "Pakistani mothers of sons are less fertile than those of daughters". However, as matters stand, we have to begin more soberly. 'This book has been there now for six years and it is rather late in the day to review it. Yet, it probably remains unknown to many readers and it does contain unusual information. The work is strong methodologically, and it applies in parts analytic methods not ordinarily used among demographers and social scientists in the English-speaking world. Most importantly, it relates Islam with fertility - analytically, seriously and respectfully. 'This reviewer is no judge of the religion-related parts of the book, but he knows the author personally. In fact, Kouaouci, a professor of demography and economic planning at the University of Algiers, spent the summer of 1988 at the University of Alberta preparing his paper for presentation to the Second African Population Conference at Dakar the following November. The author displayed not only all the external symptoms of a pious person, but carried the inner dignity and all-round friendliness of a truly religious man. More convincingly and objectively, all his important statements are generously documented in footnotes for experts to review.